Characteristic of social competence "cooperation" in schoolchildren 9-11 years old, studying in inclusive classes - Natalia Flotskaya; Svetlana Bulanova (University of Aberdeen, School of Education, 2018)
The article is devoted to inclusive education in subarctic region. The aim of the article is to find out special features of social competence "cooperation" at schoolchildren between of 9- 11 years, studying in mainstream and inclusive classes in Arkhangelsk schools. The main indicators of the social competence "cooperation" are analyzed, we have also compared these indicators at school children in inclusive and comprehensive (mainstream) classes. It is noted that almost all these indicators are lower in inclusive education than in comprehensive classes, which is due to lack of specific inclusive technologies, lack of teachers' experience working in inclusive education.